2014
DOI: 10.1016/j.tra.2013.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Residential satisfaction close to highways: The impact of accessibility, nuisances and highway adjustment projects

Abstract: In this paper we focus on gaining insight into the residential satisfaction of households near highways, based on survey data collected among 1,225 respondents in the Netherlands living within 1,000 meters from a highway. Ordinal regression was used to study the impact of highway externalities on residential satisfaction. Moreover, we gained first insights into the reactions of people on highway adjustment projects, by studying people's expectations towards residential satisfaction as a consequence of the proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
26
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 41 publications
(103 reference statements)
7
26
0
3
Order By: Relevance
“…They also confirmed that proximity to roads had no effect, in contrast to previous findings [41]. However, the negative effects recorded in the cited study may be balanced by satisfaction associated with the increases in accessibility offered by major roads [44,45]. If so, planners may be able to reduce or even eliminate dissatisfaction associated with living close to a major road by mitigating adverse factors such as noise and enhancing positive factors such as access to them.…”
Section: Built Environmentsupporting
confidence: 71%
“…They also confirmed that proximity to roads had no effect, in contrast to previous findings [41]. However, the negative effects recorded in the cited study may be balanced by satisfaction associated with the increases in accessibility offered by major roads [44,45]. If so, planners may be able to reduce or even eliminate dissatisfaction associated with living close to a major road by mitigating adverse factors such as noise and enhancing positive factors such as access to them.…”
Section: Built Environmentsupporting
confidence: 71%
“…For instance, distance to the toll gate has a negative coefficient, indicating that the closer the respondents live to the toll gate, the more satisfied they are with their current neighbourhood. This result is in line with the results of the study of Hamersma, Tillema, Sussman, and Arts (2014), who found that 85% of Dutch respondents were satisfied with living within 1 km of a highway. However, respondents in the Jakarta-Bandung region are less satisfied with the current housing conditions if they live close to the toll gate.…”
Section: Latent Variable Models For Satisfaction With Housing and Neisupporting
confidence: 91%
“…Conflicts between road infrastructure and other spatial functions, such as housing, nature and recreation, are generally acknowledged. Examples of such conflicts are negative externalities such as noise, air pollution and safety issues (Banister, Anderton, Bonilla, Givoni, & Schwanen, 2011;Hamersma, Tillema, Sussman, & Arts, 2014). Consequent ways of responding for planning and decision-making, such as protection and mitigation, are much explored.…”
Section: Content: Addressing Functional Interrelatednessmentioning
confidence: 99%